A empresa e o direito humano ao desenvolvimento: inovação e sustentabilidade à luz da agenda 2030 - Gomez, Alejandro Martins Vargas (2024)
This research aims to analyze, in the current global system of collaboration and coordination between States, companies and civil society, the issue of human development, given that, even after so many international documents on human rights, we still face the challenge of social inequality and of poverty. By differentiating human development from economic growth, and using the Human Development Index as a basis and not the Gross Domestic Product of each country, according to the lessons of Amartya Sen, it is possible to achieve a more equitable State through the right to development. The initial question we sought to address was understanding the meaning of development and how it applies to Law, differentiating it from mere economic growth. Furthermore, we seek to analyze the constitutional principles of the Brazilian economic order and critically evaluate the implementation of Sustainable Development Goal n. 9 in Brazil, through the analysis of the Luz Reports (from 2017 to 2024) and the first edition of the Brazilian Innovation and Development Index (IBDI), launched in 2024, which demonstrate the panorama of Brazilian business innovation and its challenges in achieving Agenda 2030. The present study uses the hypothetical- deductive method, supported by national and international bibliographical and documentary research on the topic. It is concluded that when the company complies with human rights, it generates sustainable human development.